2006
DOI: 10.1590/s1519-38292006000100015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do consumo alimentar de crianças pertencentes a uma creche filantrópica na Ilha de Paquetá, Rio de Janeiro, Brasil

Abstract: OBJETIVOS: comparar o consumo alimentar de pré-escolares, pertencentes a uma creche filantrópica, em dois períodos (no ato da matrícula e após seis meses), com base na proposta da Pirâmide Alimentar Infantil Norte-Americana e através do Índice de Alimentação Saudável (IAS). MÉTODOS: relativamente à avaliação dietética, foi utilizada a história alimentar da criança com o responsável, no ato da matrícula; após seis meses de frequência da criança, utilizou-se o método de pesagem de alimentos (na creche) e registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
14

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 12 publications
0
7
0
14
Order By: Relevance
“…In addition, most studies of the child population are usually held in public health institutions and at nursery schools 14,15,16,17,18 and few population-based studies have been conducted in recent years 19,20,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most studies of the child population are usually held in public health institutions and at nursery schools 14,15,16,17,18 and few population-based studies have been conducted in recent years 19,20,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the study outcomes and index scores, two studies did not include them 18,19 and 15 studies did not analyze them [11][12][13][14][20][21][22][23][24][25][26][27][28][29][30] . Study outcomes and index scores were found in 28 studies: seven of these evaluated the relationship of the index with socioeconomic and demographic factors and food items 17,[31][32][33][34][35][36] ; eight studies evaluated the relationship with socioeconomic factors and health [37][38][39][40][41][42][43][44] ; five studies evaluated the relationship with health outcomes [45][46][47][48][49] ; four studies evaluated the relationship with nutrients [50][51][52][53] ; two studies evaluated the relationship with some type of intervention 15,54 ; one study evaluated the relationship with nutrients and food items 55 ; and one study evaluated the relationship with socioeconomic and demographic factors …”
Section: Resultsmentioning
confidence: 99%
“…Regarding dietary surveys, 36 studies (80%) used a 24-hour recall; three used a food frequency questionnaire (FFQ); one study used food history; and five studies used more than one food survey. Barbosa et al 20 used food history, direct food weighing and food registration; Domene et al 31 used direct food weighing and 24-hour recall; Sampaio 13 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations